2020
DOI: 10.1002/jper.19-0620
|View full text |Cite
|
Sign up to set email alerts
|

Management of medication‐related osteonecrosis of jaw: Comparison between icariin and teriparatide in a rat model

Abstract: Background The aim of this study is to compare the effects of icariin and teriparatide on the treatment of medication‐related osteonecrosis of the jaw (MRONJ) using a rat model. Methods Fifty rats undergoing ovariectomy were randomly assigned to control group (n = 10) and the MRONJ model group (n = 40). Zoledronic acid (0.2 mg/kg) and dexamethasone (2 mg/kg) were injected into rats in the model group for 8 weeks while saline was applied in control group, then all rats underwent tooth extraction and bone defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“… Bone exposure 30 , 44 , 45 , 47 , 62 , 64 , 67 , 72 , 93 96 Indicated by the area, time of bone exposure. Histopathological assessments Healing conditions 59 , 60 , 63 , 98 Histological sections show the soft tissue healing with the distance between the edges of the epithelia, and bone defects with the length of the necrotic bone exposed towards the oral cavity. Necrotic bone 49 , 57 – 59 , 64 , 69 , 72 , 96 , 100 The presence of necrotic bone represents the occurrence of MRONJ.…”
Section: Assessment Of Mronj-like Lesions In Rodent Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“… Bone exposure 30 , 44 , 45 , 47 , 62 , 64 , 67 , 72 , 93 96 Indicated by the area, time of bone exposure. Histopathological assessments Healing conditions 59 , 60 , 63 , 98 Histological sections show the soft tissue healing with the distance between the edges of the epithelia, and bone defects with the length of the necrotic bone exposed towards the oral cavity. Necrotic bone 49 , 57 – 59 , 64 , 69 , 72 , 96 , 100 The presence of necrotic bone represents the occurrence of MRONJ.…”
Section: Assessment Of Mronj-like Lesions In Rodent Modelsmentioning
confidence: 99%
“…The definition of necrotic bone depends on the number of confluent empty or karyolytic osteocytic lacunae. Empty bone lacunae 30 , 45 , 95 , 96 , 98 The proportion or the number of empty bone lacunae in a certain area indicates the degree of osteocyte loss, which present the bone necrosis. TRAP + osteoclast 44 , 49 , 57 , 58 , 64 , 67 , 69 , 72 , 93 , 95 101 The TRAP + osteoclasts present the bone resorption, commonly used indicators including numbers of osteoclast per area or per bone line.…”
Section: Assessment Of Mronj-like Lesions In Rodent Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…An animal model showed that in addition to BRONJ treatment, PTH also has potential to prevent the development of jaw necrotic lesions by maintaining osteocyte survival ( Kuroshima et al, 2014a ). The administration of teriparatide led to a higher ratio of RANKL-positive osteocytes ( Liu J. et al, 2020 ). Another study that applied different doses of teriparatide suggested that its therapeutic effect may not be dose dependent ( Yu and Su, 2020 ).…”
Section: Therapeutic Application Of Parathyroid Hormone/parathyroid Hormone-related Protein In Orofacial Regionmentioning
confidence: 99%